Effectiveness of Apu-Organic Liquid Fertilizer (Pistia stratiotes L.) on Ipomoea reptans Poir. Growth - Ambar Pratiwi; Arni Isma Nurrohmi (Universitas Negeri Surabaya, 2020)
Fertilization uses organic fertilizers made of Apu-apu (Pistia stratiotes L.) can support nutrient availability there by increasing soil fertility. P. stratiotes L. contains nutrients but in elemental form that is not yet available. So far, the abundance of P. stratiotes L. has not been utilized properly by the society, hence that research is needed to make liquid organic fertilizer P. stratiotes L. by fermentation. The purpose of this study was to determine the increase in the growth of Ipomoea reptans Poir. by giving apu-apu liquid organic fertilizer and determine the optimum concentration of liquid organic fertilizer for apu-apu for the growth of ground water spinach. This research was conducted at the Kemusuh Green House, Banyurejo, Tempel, Sleman. The independent variable used was the POC concentration of Apu-apu plants with five replications and six levels of treatment (K = 0%, P1 = 4%, P2 = 8%, P3 = 12%, P4 = 16% and P5 = 20%). The data obtained were analyzed using ANOVA followed by the Duncan Test. Apu-apu liquid organic fertilizer contains elements C (4.6%), N (0.07%), P (0.09%) and K (0.07%). The application of liquid organic fertilizer made from apu-apu has an effect on the growth of water spinach on the parameters of the number of leaves, leaves width, fresh weight and chlorophyll content. The conclusion obtained from the results of this study is that the application of liquid organic fertilizer apu-apu provides an increase in the growth of ground water spinach.